Host-directed therapies in pulmonary tuberculosis: Updates on anti-inflammatory drugs - Cubillos-Angulo, Juan M.; Nogueira, Betânia M. F.; Arriaga, María B.; Barreto-Duarte, Beatriz; Araújo-Pereira, Mariana; Fernandes, Catarina D.; Vinhaes, Caian L.; Villalva-Serra, Klauss; Nunes, Vanessa M.; Miguez-Pinto, João P.; Amaral, Eduardo P.; Andrade, Bruno B. (Frontiers in Medicine, 2022)
Tuberculosis (TB) is a lethal disease and remains one of the top ten causes of mortality by an infectious disease worldwide. It can also result in significant morbidity related to persistent inflammation and tissue damage. Pulmonary TB treatment depends on the prolonged use of multiple drugs ranging from 6 months for drug-susceptible TB to 6–20 months in cases of multi-drug resistant disease, with limited patient tolerance resulting from side effects. Treatment success rates remain low and thus represent a barrier to TB control. Adjunct host-directed therapy (HDT) is an emerging strategy in TB treatment that aims to target the host immune response to Mycobacterium tuberculosis in addition to antimycobacterial drugs. Combined multi-drug treatment with HDT could potentially result in more effective therapies by shortening treatment duration, improving cure success rates and reducing residual tissue damage. This review explores the rationale and challenges to the development and implementation of HDTs through a succinct report of the medications that have completed or are currently being evaluated in ongoing clinical trials.